THE EFFECT OF SOCIAL SECURITY AND CAREER DEVELOPMENT ON THE WORK COMMITMENT - Haryati , Endri (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2024)
This study purposed to test the influence of sosial insurance and simultaneous careeer development that hadsignificant influence to employee commitmen in PT. Petrokimia Gresik. The variables that are analyzed as affected factor that influence the workcommitmennt were social insurance (x1) and career development (x2). The population in this study was 81 employees and the sample was 81 employees. For data collection technique. The writer used questionnaires, documentation, interview, observation, and statiscal analysis using linear regresaion. Based on the data analysis technique, it could be concluded that there were significant simultaneous social insurance that was influence work commitment on the employees of PT. Petrokimia Gresik Tbk. It could be seen by t-test where the test obtained the significant value on work commitment of the employees in PT. Petrokimia Gresik. Career development and sosial insurance had a simultaneous effect on employees of PT. Petrokimia Gresik. it can be evidenced by f-test where the test obtained significant value. This was intented to guarantee social insurance and career development should be concerned on PT Petrokimia Gresik to improve and support the directness business and target of the company. Thus if it could be noticed and applied in the company, an employee or employees would always give the best work for the company.